قياس الالتزام التنظيمي لدى العاملين في قطاع التعليم العالي دراسة مقارنة بيين عمال المدرسة العليا للاساتذة و عمال جامعة عمار ثليجي بالأغواط - بوقناشة ياسمين; ساري كريمة; بوفاتح محمد (My University, 2023)
The study aimed to identify the level of organizational commitment among workers in the higher education sector (university, high school), where the descriptive approach was used, and the study sample consisted of 48 employees between (university, high school). The following results: •The level of organizational commitment among workers is high. •There are no differences in the level of organizational commitment among workers due to gender. •There are no differences in the level of organizational commitment among workers due to the workplace. Keywords: organizational commitment, workers, higher education sector.